1978
DOI: 10.1159/000212244
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxy-Vitamin D, Diet and Sunlight Exposure in Patients Admitted to a Geriatric Unit

Abstract: Dietary intake, sunlight exposure and 25-hydroxy-vitamin D levels were estimated in 62 patients admitted to a geriatric assessment unit. There was a significant correlation between vitamin D intake and 25-hydroxy-vitamin D levels but none between sunlight exposure and these. This suggests that in old age dietary deficiency may be a more important cause of metabolic bone disease than limited sunlight exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

1979
1979
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 8 publications
2
7
1
Order By: Relevance
“…Since women with either low or normal 25OHD levels had similar dietary vitamin D intakes, our results indicate that in white postmenopausal females, vitamin D deficiency is primarily accounted for by diminished sunlight exposure. On the other hand, in agreement with previous reports (15)(16)(17), the positive correlation between 25OHD and dietary vitamin D intake noted in individuals with low 25OHD suggests that in this subset of women, circulating 25OHD levels are primarily dependent on dietary sources. However, the vitamin D intake is apparently inadequate to compensate for the lack of sunshine exposure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since women with either low or normal 25OHD levels had similar dietary vitamin D intakes, our results indicate that in white postmenopausal females, vitamin D deficiency is primarily accounted for by diminished sunlight exposure. On the other hand, in agreement with previous reports (15)(16)(17), the positive correlation between 25OHD and dietary vitamin D intake noted in individuals with low 25OHD suggests that in this subset of women, circulating 25OHD levels are primarily dependent on dietary sources. However, the vitamin D intake is apparently inadequate to compensate for the lack of sunshine exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Historically, most of the studies on vitamin D deficiency were performed in elderly populations of Northern Europe (13)(14)(15)(16)(17)(18). In the United States, because of the lower latitude and food supplementation, vitamin D deficiency is not commonly regarded as an important clinical problem (12,19), and consequently, not much effort has been devoted to evaluating the vitamin D status of the elderly population in this country.…”
mentioning
confidence: 99%
“…The rela tively low but significant correlation between the dietary vitamin D intake and the 25-OH-D concentrations indicates that the method used in this study for estimating vitamin D intake was good as the intraindividual varia tions are minimized. The correlation coeffi cient is comparable to that reported by Nayal et al [21] and Haddad and Hahn [22], Taking together the 25-OH-D concentra tions in serum, the estimated daily intake of vitamin D and the exposure to sunlight it can be stated that the long-stay geriatric patients suffer from vitamin D deficiency due both to deficient dietary intake and to lack of sun shine. This view is further supported by the observation of Guillemant et al [23] who did not find any significant impaired absorption of vitamin D from the intestine in elderly people as compared with young adults.…”
Section: Discussionsupporting
confidence: 86%
“…However, a positive correlation be tween dietary vitamin D intake and serum 25-OH-D concentration has been docu mented in many studies, thus indicating that dietary vitamin D could be of importance at least in Northern countries such as Finland and the Scandinavian countries [22][23][24]. In the present study, no correlation between vi tamin D intake and serum 25-OH-D concen tration was found.…”
Section: Discussioncontrasting
confidence: 68%